Next-Generation Self-Powered Photodetectors using 2D Bismuth Oxide Selenide Crystals - Roy, Pradip Kumar; Mosina, Kseniia; Hengtakaeh, Sofia; Sarkar, Kalyan Jyoti; Mazánek, Vlastimil; Luxa, Jan; Sofer, Zdenek (ACS applied nano materials, 2024)
The concept of self-powered photodetectors has attracted significant attention due to their versatile applications in areas such as intelligent systems and hazardous substance detection. Among these, p-n junction and Schottky junction photodetectors are the most widely studied types; however, their fabrication processes are often complex and costly. To overcome these challenges, we focused on the emerging self-powered, ultrasensitive photodetector platform based on photoelectrochemical (PEC) principles. This platform leverages the unique properties of the emerging material bismuth oxide selenide (Bi2O2Se), which features a wide bandgap (∼2 eV) and a high absorption coefficient. We utilized chemical exfoliation to obtain thin layers of Bi2O2Se, enabling highly efficient photodetection. The device characterization demonstrated impressive performance metrics, including a responsivity of 97.1 μA W-1 and a specific detectivity of 2 × 108 cm Hz 1/2 W-1. The PEC photodetector also exhibits broad-spectrum sensitivity, from blue to infrared wavelengths, and features an ultrafast response time of ∼82 ms and a recovery time of ∼86 ms, highlighting its practical potential. Moreover, these self-powered photodetectors show excellent stability in electrochemical environments, positioning them promising candidates for integration into future high-efficiency devices.